Personalized Al-Quran Memorization Testing System Using Group Decision Support System - Rian Adam Rajagede; Yuanda Hanif Hisyam; Muhammad Ichlasul Amal Yulianto; Farid Amin Ridwanto; Alfian Try Putranto; Muhammad Rifqi Fatchurrahman Putra Danar (Aceh International Journal of Science and Technology, 2021)
Memorizing Al-Quran is one of the most important acts of worship for Muslims. After memorizing some parts of the Al-Qur’an, the hafiz or Al-Qur’an’s memorizer is recommended to repeat or muraja’ah their memorization to strengthen it. This process is usually done in pairs by listening to each other’s memorization or testing by asking questions about Al-Quran. This study proposes a system that can help memorizers test their memorization independently without a partner. The system will perform a memorization test to support the user’s process of memorizing the Al-Quran. The system records and analyzes user data and uses it to personalize memorization testing from time to time. The system was made using the Group Decision Support System (GDSS) approach with the help of several Al-Quran memorizers as decision-makers. The GDSS algorithm used combines Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and Weighted Geometric Mean to rank surahs based on provided user data. The evaluation was conducted with the help of human evaluators, and the evaluators showed 78% agreement with the system decision.